2003
DOI: 10.1097/01.tp.0000061600.74982.0d
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of renal graft function by perioperative monitoring of cortical microcirculation in kidney transplantation.1

Abstract: Thermodiffusion could be clinically applicable for the perioperative monitoring of renal graft perfusion. Intraoperative reduction of cortical microcirculation has a high predictive value with respect to detection of delayed renal function. Postoperatively, impaired renal microperfusion is associated with acute tubular necrosis. Living-related donor grafts show less microcirculatory alteration than cadaveric kidneys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
(25 reference statements)
3
21
0
Order By: Relevance
“…Microcirculation is a characteristic parameter of organ function and viability as already demonstrated by Anelescu and colleagues, who showed that microcirculatory derangements after reperfusion in the kidney correlate with impaired graft function after transplantation 30. Indeed, combining the deleterious effects of BD and IRI, microcirculation assessed by IVFM was dramatically impaired when organs from BD donors were transplanted and reperfused for 2 h as compared to naïve or sham control animals (Figure 2B and C).…”
Section: Discussionsupporting
confidence: 61%
“…Microcirculation is a characteristic parameter of organ function and viability as already demonstrated by Anelescu and colleagues, who showed that microcirculatory derangements after reperfusion in the kidney correlate with impaired graft function after transplantation 30. Indeed, combining the deleterious effects of BD and IRI, microcirculation assessed by IVFM was dramatically impaired when organs from BD donors were transplanted and reperfused for 2 h as compared to naïve or sham control animals (Figure 2B and C).…”
Section: Discussionsupporting
confidence: 61%
“…Macrocirculation can decisively influence microcirculation, which itself is a determining factor in organ quality and graft viability. Anelescu and colleagues could show that microcirculatory derangements after reperfusion in the kidney correlate with impaired graft function after transplantation (19). The same group demonstrated the importance of microcirculatory events in predicting primary graft failure by intraoperative quantification of liver perfusion (20).…”
Section: Discussionmentioning
confidence: 99%
“…The different perfusion intensities in different regions of the renal cortex suggest uneven distribution of resistance to renal microcirculation in DGF patients, which may be related to the pathological changes of terminal vasculature induced by ischemic reperfusion in the transplanted kidney (Inman et al, 2003;Huang et al, 2002). This may also be the mechanism of difference in the study by Angelescu et al (2003) (Figure 1). …”
Section: Discussionmentioning
confidence: 91%
“…Using a thermal dissipation probe inserted into the cortex of the transplanted kidney, Angelescu et al (2003) found lower microcirculatory perfusion in DGF patients than in patients with a normally functioning transplanted kidney. In addition, ischemic reperfusion has been shown to result in increased serum levels of endothelin and endothelin-1, but decreased levels of the vasodilator nitric oxide, which increases vascular resistance in the transplanted kidney (Schilling et al, 1996;Huang et al, 2002;Inman et al, 2003;Perico et al, 2004;Zlotnick et al, 2010).…”
Section: Discussionmentioning
confidence: 99%